Analisis Pengaruh Content Marketing, Live Marketplace dan Diskon Harga untuk Melakukan Keputusan Pembelian Skintific di Shopee terhadap Kepercaayaan Konsumen sebagai Variabel Intervening - Putri Dewi Lestari; Henry Casandra Gultom; Prianka Ratri Nastiti (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to evaluate the influence of Content Marketing, the Live Marketplace feature, and discounts on purchasing decisions for Skintific skincare products on the Shopee platform, with consumer trust as an intermediary variable. The background of this study is based on the increasing use of marketplaces in online shopping activities, as well as the increasing trend of self-care as part of the lifestyle of the younger generation, especially students. This development encourages business actors to implement effective digital marketing strategies, including through social media, engaging content, and interactive features available on marketplaces such as Shopee. This study uses a quantitative approach with a survey method. Respondents in this study were students at the University of the Indonesian Teachers Association (UPGRIS) Semarang who had purchased Skintific products through the Shopee platform. Data were collected using a closed-ended questionnaire and analyzed using path analysis techniques using statistical software. The results show that Content Marketing and the use of the Live Marketplace feature have a positive and significant influence on consumer trust. Consumer trust is proven to be an important factor that significantly influences purchasing decisions. Conversely, discounts do not have a direct effect on purchasing decisions, but have a significant indirect impact when mediated by consumer trust. These findings indicate that emotional aspects and perceived trust in the brand are more dominant in influencing purchasing behavior than discount factors alone. Overall, this study emphasizes the importance of implementing appropriate and integrated digital marketing strategies, especially through content marketing and utilizing the Live Marketplace feature, in building consumer trust and driving product purchasing decisions on e-commerce platforms.